Penyuluhan Tentang Penyakit Ispa Di Wilayah Dusun 4 Desa Sumber Sari Kecamatan Kabawetan Tahun 2025 - Lestari, Devika; Larasati, Dina; Desmita, Elmi Dwi; Monica, Elsa; Rustandi, Handi; Sari, Fikitri Marya; Epriana S, Meri; Rohani, Tuti; Azissah, Danur (LPPM Universitas Dehasen Bengkulu, 2025)
ISPA is one of the most common diseases in Indonesia, but there are still many people who do not understand the proper prevention and treatment. By increasing public knowledge and behavior in the prevention and treatment of ISPA through counseling. The method used in the research process is a lecture system. ISPA counseling can significantly increase public knowledge and behavior in the prevention and treatment of ISPA. ISPA counseling is one of the effective strategies in increasing public knowledge and behavior in the prevention and treatment of ISPA. Therefore, it is necessary to conduct continuous and extensive ISPA counseling to increase public awareness and knowledge about ISPA.